Starting an academic career in Mexico: experiences of young researchers at public universities - Barreras Beltrán, Carlos Alberto (2026)
This study aims to analyze the experiences of newly appointed academic staff during their entry into the academic career at public universities in Mexico. Using a qualitative approach, semi-structured interviews were conducted with 21 newly appointed academics from two public universities in northwestern Mexico to examine the transition to tenure and the factors that influence institutional adaptation and scientific output. Sampling was by convenience and selection criteria, based on participants' recognition as researchers. An interpretive phenomenological perspective was employed, and the results were analyzed through the construction of analytical themes and organized into categories of analysis. The results reveal differentiated trajectories determined by prior experience, appointments, and the organizational culture of the departments. Two pathways to integration are identified: one abrupt, marked by administrative overload, and another gradual, which favors the continuity of scientific work. Furthermore, institutional norms and teaching incentive programs create a context that can limit research development, particularly among those lacking institutional capital. The study concludes that induction, support, and mentoring programs are needed for academic staff in their initial stages, along with an analysis of incentive policies and infrastructure conditions in Mexican Higher Education Institutions (HEIs). Successful integration into an academic career depends not only on individual merit but also on the alignment between institutional culture, community support, and organizational recognition.